Coincidence of Large Adrenal Cyst and Prominent Hyporeninemic Hyperaldosteronism - Takaaki Sakaue; Yosuke Okuno; Kosuke Mukai; Shingo Fujita; Junji Kozawa; Hitoshi Nishizawa; Taka-Aki Matsuoka; Hiromi Iwahashi; Maeda Norikazu; Yuto Yamazaki; Hironobu Sasano; Michio Otsuki; et al. (Case Reports in Endocrinology)
A 67-year-old Japanese woman who had end-stage renal disease was referred to our hospital for kidney transplantation. Abdominal CT revealed a large adrenal mass with inhomogeneity. She had a history of hospitalization for stroke and heart failure and exhibited prominent hyporeninemic hyperaldosteronism. Histological examination of the resected tumor with anti-CYP11B2 antibody indicated that she had a vascular endothelial cyst with primary aldosteronism (PA) due to multiple adrenocortical micronodules. This report implicates the pathological interaction between adrenal vascular cysts and PA-mediated vascular damage of the adrenal vein.